2014
DOI: 10.1371/journal.pone.0097299
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Eye Tracking Based Metrics for Infant Gaze Patterns in the Face-Distractor Competition Paradigm

Abstract: ObjectiveTo develop new standardized eye tracking based measures and metrics for infants’ gaze dynamics in the face-distractor competition paradigm.MethodEye tracking data were collected from two samples of healthy 7-month-old (total n = 45), as well as one sample of 5-month-old infants (n = 22) in a paradigm with a picture of a face or a non-face pattern as a central stimulus, and a geometric shape as a lateral stimulus. The data were analyzed by using conventional measures of infants’ initial disengagement f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Several studies have shown the value of remote eye tracking in vulnerable populations of children, to infer attentional or psychological capacities 9,12,18 . Whereas most studies rely on behavioral observations and the use of instructions, a distinct feature of the current paradigm is the nonverbal, quantitative approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the value of remote eye tracking in vulnerable populations of children, to infer attentional or psychological capacities 9,12,18 . Whereas most studies rely on behavioral observations and the use of instructions, a distinct feature of the current paradigm is the nonverbal, quantitative approach.…”
Section: Discussionmentioning
confidence: 99%
“…This information is obtained by calculating quantitative parameters based on temporal and spatial properties of eye movement responses. Examples of such parameters are reaction time 13 , fixation time 17 , saccade metrics 7 or cumulative attention allocation 18 . The availability of these parameters is new to the field of visual assessment in children at a young developmental stage.…”
Section: Introductionmentioning
confidence: 99%
“…The eye-tracking test was designed to assess infants' attention to nonface patterns and faces by using a face-distractor competition paradigm [31,40]. In this paradigm, infants fixate a nonface pattern or a picture of a face in the center of the screen while a lateral distractor stimulus (geometric shape) is presented to the left or to the right.…”
Section: Eye-trackermentioning
confidence: 99%
“…Before running the actual study protocol, a calibration procedure was performed as explained in detail by Ahtola et al [31]. The eye-tracking protocol constituted 32 trials.…”
Section: Eye-trackermentioning
confidence: 99%
See 1 more Smart Citation